Identification and Selection of Entomopathogenic Fungi as Biocontrol Agents for Aphis gossypii from South Sumatra - SITI HERLINDA; CHANDRA IRSAN; REKA MAYASARI; SELLY SEPTARIANI (Microbiology Indonesia, 2010)
Aphid, Aphis gossypii is a vector of curly virus disease. The damage of chili due to its feeding  is only 35% and it can achieved 100% if the damage caused by the aphid as a vector.  The objectives of this research were to explore, to isolate, to identify, and to select entomopathogenic fungi as biocontrol agents for A. gossypii. The fungi were explored using insect bait in soil and collected infected insects from South Sumatra, Indonesia.  Then, the fungi were isolated and identified, and finally the bioefficacy tests were done using 1 x 106 conidia mL-1 against the third instar of A. gossypii. The explorations found 25 isolates of enthomopathogenic fungi consisting 10 isolates of Beauveria bassiana and 15 isolates of Metarhizium anisopliae. Selection of the fungi isolates on the aphid nymphs showed that isolate BPM isolated from Pseudoplusia chalcites caused the highest mortality rate (80.80%), while the lowest (47.20%) was caused by the isolate BAgTb isolated from A. gossypii.  The shortest time needed to produce 50% mortality (Lethal Time 50) was 2.54 days (isolate of Chrysodeixis chalcites from Muarasiban). The longest time (3.66 days) was produced by isolate of Tenebrio molitor from Tanjung Raja.